Superhydrophobic concrete with enhanced mechanical robustness: Nanohybrid composites, strengthen mechanism and durability evaluation. (30th June 2020) - She, Wei; Yang, Jingxian; Hong, Jinxiang; Sun, Dewen; Mu, Song; Miao, Changwen
Graphic abstract: Highlights: A robust superhydrophobic concrete was fabricated by a nanohybrid method. Non-wettability was improved by creating a nano/micro two hierarchical structure. The strengthen effects of the nanosilica increased mechanical resistance of surface. Abstract: Although biomimetic designs (lotus effect) are likely to play a pivotal role in exploring future breathable super waterproof surfaces to increase the durability of reinforced concrete, facile fabrication of mechanically durable superhydrophobic concrete surface remains a big challenge. Here, we describe a multipronged nanohybrid method to build robust superhydrophobic concrete that combine surficial hydrophobization and morphological modification based on silanized nano-silica simultaneously. Experimental results show that the non-wettability can be significantly improved by turning the surface roughness from primarily microscopic features into nano/micro two hierarchical structure. Combined with the densification (filling effect) and strengthen (pozzolanic reaction) effects of the nano-silica, the increased wear resistance is achieved by building nano/micro roughness which is protected to some extent by large scale feature and, the hydrophilic defects are effectively prevented by using penetrating waterproof agent. Moreover, the relevant microstructural strengthen mechanism is discussed and the durability of modified surface is also evaluated.